"Inter and Enter: An Invitation to Collaboration Thru Autoethnography". Issue 4 (February 2023) - Alexander, Bryant K.; Hernandez, Carmen G.; Pelias, Ronald J.; Alhayek, Katty; Poulos, Christopher; Moreira, Claudio; Sutton, Timothy; Stephenson, Ayshia; Foster, Elissa; Twishime, Porntip I.
This performative and collaborative autoethnography plays with the homophonic or maybe homiletics of "inter" and "enter" as the invitational aspect of collaborative autoethnography. The contribution of diverse collaborators from differing racial, ethnic, geo-spatial locations, and generational standpoints speak to/between experiences with the dialogic aspects of autoethnography; the speaking of self with and for others that is always a part of autoethnographic practice, now made salient in the intentional collaborative, thus exploring the interpersonal, interracial, international, intersectional, interstitial, and the symbolic interactional aspects of autoethnography.